Análise elastoplástica micromecânica de cotovelos de tubos compósitos de matriz metálica pressurizados - Pinheiro, Leonardo Fernandes (2023)
Metal matrix composites (CMMs) are composite materials formed by a metallic matrix and reinforcements dispersed in its microstructure. These reinforcements are mostly carbon fibers, ceramic inclusions or phase variations within the metal matrix itself. When these materials are subjected to pressure, elastoplastic deformations occur at a microscopic level, which directly influence the macroscopic behavior of the structure. Micromechanical elastoplastic analysis seeks to understand how these deformations occur and how they affect the mechanical properties of the material, with the aim of optimizing its performance in practical applications. It was proposed in this work, the implementation of a micromechanical elastoplastic model in the form of subroutines to be used in the commercial finite element software ABAQUS. The proposed constitutive model was validated with test data available in the literature and then used in the analysis of pipe elbows subjected to bending efforts and internal pressure. The results showed that ceramic inclusion and internal pressure act directly in determining the limit forces of the elbows, making it possible to determine analytical relationships that are capable of determining these values.